Activity Profile and Physical Performance of Match Play in Elite Futsal Players - Ribeiro, João Nuno; Gonçalves, Bruno; Coutinho, Diogo; Brito, João; Sampaio, Jaime; Travassos, Bruno (Frontiers in Psychology, 2020)
Understanding the physical demands of futsal requires a precise quantification of the players’ activities during match play.This study aimed to: (1) describe external load, identifying differences between the 1st and 2nd halves in official futsal matches; (2) identify the most important external workload metrics to profile the players; and (3) identify the collinearity between variables in the analysis of physical performance of futsal players. Match external load data were collected from male players (n = 28) in six games of the Final Eight of the Portuguese Futsal Cup 2018. The players increased the distance covered per min at 12-18 km/h in the 2nd half (p < .01). Dynamic stress load also increased in the 2nd half (p = 0.01). The variables that best predicted the physical profile of each player were decelerations (predictor importance, PI=1), walking (PI=1), sprinting (PI=1), jogging (PI=0.997), total distance covered per minute (PI=0.992) and metabolic power (PI=0.989). Decelerations showed a highest association with the clusters levels (p<0.001; PI=1); this suggests decelerations as a potential candidate for best analysing the physical load of futsal players. Overall, the data from this exploratory study suggest that distance covered per minute (m.min-1), number of sprints (>18 Km/h), decelerations (>-2 m/s-2) and metabolic power (W/Kg) are the variables that most discriminate load intensity of elite futsal players.